ANALISIS NILAI-NILAI BUDAYA JAWA DALAM FILM BADARAWUHI (2024) - Andriana, Noni Puspa; Sa'idah, Zahrotus (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
Badarawuhi (2024) is a 122-minute horror film that not only features horror elements, but also highlights Javanese cultural values. However, not all viewers realize the existence of these symbols because some of them are conveyed implicitly. The Javanese cultural symbols presented in this film indirectly function as a medium to introduce or provide insight into Javanese culture to the audience. Research related to this film was conducted with a qualitative approach through three stages of data collection, namely non participant observation, literature study, and supporting documents such as news articles and journals. The process of data analysis with data collection, data reduction, data display, conclusion drawing. This researcher identified the representation of East Java’s cultural identity which includes customs, traditions, and local beliefs. The results show that cultural values in the Java region, especially East Java, reflect strong traditional cultural elements. This provides a more in-depth picture of the richness of Javanese culture raised in the movie Badarawuhi (2024).